Piebaldism: A brief report and review of the literature - Saurabh Agarwal; Amit Ojha (Wolters Kluwer Medknow Publications, 2012)
Piebaldism is a rare autosomal dominant disorder of melanocyte development characterized by a congenital white forelock and multiple symmetrical stable hypopigmented or depigmented macules. We report a family with piebaldism affecting three successive generations and also review the literature.